LATIN SONG AT THE ABBEY OF SANKT GALLEN FROM C. 800 TO THE LIBER YMNORUM. (October 2019) - Barrett, Sam
Abstract : New light is shed on the song culture of Sankt Gallen almost a century before its earliest notated sources through consideration of the poetic section of a manuscript copied at the Abbey shortly after the year 800, i.e. the second part of Leiden, Universiteitsbibliotheek Vossianus Lat. Q. 69. The predominantly Merovingian accentual Latin verse ( rhythmi ) and metrical verse by the late-antique poet Prudentius (his Liber Cathemerinon and Liber Peristephanon ) were written out in song forms. It is newly proposed that Prudentius' verse from the Liber Peristephanon was arranged into a liturgical cycle. The poetic section of the Leiden manuscript is accordingly understood as a collection of songs, which prompts reflection on the way in which earlier sung versus at Sankt Gallen may have provided models for the later Liber ymnorum . Witnesses to the song culture of Sankt Gallen in the first half of the ninth century are re-examined and a leading role during this period for the nearby Abbey of Reichenau is proposed. Finally, it is suggested that Iso's advice to Notker that singulae motus cantilenae singulas syllabas debent habere was at least partly informed by the existing tradition of sung versus at both abbeys.